Technical and Economic Evaluation of Agricultural Waste-Based Biological Agents for Laboratory-Scale Ammonia Removal - Wiratama, Ihsan; Suhirman, Suhirman; Arvianto, Rizky Ibnufaatih; Nainggolan, Denny Hendrik; Puteri, Denanda Clarasati; Putra, Muhammad Iqbal; Luthfi, Muhammad Zulfikar (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Ammonia contamination in water poses serious ecological risks, while commercial bioremediation agents remain costly for widespread application. This study evaluated the technical and economic performance of a self-formulated biological agent made from golden apple snail shells and banana pseudostems for ammonia removal. A laboratory-scale preliminary experiment used 500 mL batch reactors containing synthetic wastewater in a 2 × 3 × 3 factorial design without replication, comparing EM4 and the self-formulated agent at initial ammonia concentrations of 10, 30, and 50 ppm over 1, 2, and 3 days. Ammonia was measured by the Nessler spectrophotometric method and analyzed using ANOVA GLM. The self-formulated agent showed performance comparable to EM4, with both achieving more than 80% removal under suitable conditions. Removal efficiency was influenced by the interaction between ammonia load and contact time, while cost analysis indicated a potential 92.1% saving. Further replicated pilot-scale studies with abiotic controls and real wastewater are recommended.